Multi-condition simulation analysis of a sliding hydraulic support system based on elastoplastic mechanics - Changji Wang; Wanting Wang; Yu Guo; Dewang Zhao (Scientific Reports)
Abstract In response to the challenges of supporting fractured and weak surrounding rock in deep coal mines in the Huainan region of China, a self-moving hydraulic support system for roof support was designed and developed. This innovative solution addresses the difficulties encountered in providing continuous support to roof structures. Based on the theory of elastoplastic mechanics, a numerical analysis model was established to calculate the mechanical parameters such as the displacement, stress, and strain of hydraulic supports during the stepping process under multiple operating conditions. The results of the numerical simulation were compared and verified with those from an actual working site. The results show that the maximum equivalent stress is 245.33 MPa for operating condition 1, 246.82 MPa for operating condition 2, and 245.27 MPa for operating condition 3. The maximum stress values under the three working conditions do not exceed the yield strength of the material, satisfying the requirements for normal bracket support operations. These research findings can establish a theoretical framework for the comprehensive assessment of the reliability and stability of hydraulic supports and the optimization of construction processes.